Investigation of ion exchange properties of natural clinoptilolite as a sorbent of Cs-137 - Пaновa Е.Н.; Буленовa К.Ж.; Блынский, П.А.; Кенжина, И.С. (Recent Contributions to Physics, 2018)
Cs-137 and Sr-90 are one of the most dangerous artificial radionuclides in contact of liquid radioactive waste (LRW) with the environment. Both radionuclide are highly mobile in the environment and can distribute for a long distances in the groundwater system. One way to protect the environment from artificial radionuclides is to use available natural sorbents. This paper presents the results of a study of ion-exchange properties of natural clinoptilolite of Chankanay deposit (hereinafter – KLT) and the possibility of its use as a sorbent for the purification of groundwater from artificial radionuclides.